A High-Throughput Extraction and Analysis Method for Steroidal Glycoalkaloids in Tomato - Dzakovich, Michael P.; Hartman, Jordan L.; Cooperstone, Jessica L. (Frontiers in Plant Science, 2020)
Tomato steroidal glycoalkaloids (tSGAs) are a class of cholesterol-derived metabolites uniquely produced by the tomato clade. These compounds provide protection against biotic stress due to their fungicidal and insecticidal properties. Although commonly reported as being anti-nutritional, both in vitro as well as pre-clinical animal studies have indicated that some tSGAs may have a beneficial impact on human health. However, the paucity of quantitative extraction and analysis methods presents a major obstacle for determining the biological and nutritional functions of tSGAs. To address this problem, we developed and validated the first comprehensive extraction and UHPLC-MS/MS quantification method for tSGAs. Our extraction method allows for up to 16 samples to be extracted simultaneously in 20 minutes with 93.0 ± 6.8% and 100.8 ± 13.1% recovery rates for tomatidine and alpha-tomatine, respectively. Our ultra-high-performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) method was able to chromatographically separate analytes derived from 16 tSGAs representing 9 different tSGA masses, as well as two internal standards, in 13 minutes. Tomato steroidal glycoalkaloids that did not have available standards were annotated using high resolution mass spectrometry as well as product ion scans that provided fragmentation data. Lastly, we utilized our method to survey a variety of commonly consumed tomato-based products. Total tSGA concentrations ranged from 0.7 to 3.4 mg/serving and represent some of the first reported tSGA concentrations in tomato-based products. Our validation studies indicate that our method is sensitive, robust, and able to be used for a variety of applications where concentrations of biologically relevant tSGAs need to be quantified.